Pharmacological Inhibition of HDAC6 Attenuates NLRP3 Inflammatory Response and Protects Dopaminergic Neurons in Experimental Models of Parkinson’s Disease - Yan, Shaoqi; Wei, Xinbing; Jian, Wencheng; Qin, Yue; Liu, Jia; Zhu, Shaowei; Jiang, Fan; Lou, Haiyan; Zhang, Bin (Frontiers in Aging Neuroscience, 2020)
Aim To investigate the role of histone deacetylase 6 (HDAC6) deacetylation activity in nucleotide-binding oligomerization domain and leucine-rich repeat pyrin 3 domain (NLRP3) inflammatory response and explore the effects of pharmacological inhibition of HDAC6 with tubastatin A (TBA) on dopaminergic injury. Methods Using 6-OHDA-induced Parkinson’s disease (PD) models, we examined the effects of TBA on NLRP3 activation and cell injury in SH-SY5Y cells. We also investigated the effects of TBA on NLRP3 inflammatory responses and dopaminergic injury in the nigrostriatal system in mice and analyzed the acetylation levels of peroxiredoxin2 (Prx2) and oxidative stress. Results TBA inhibited 6-OHDA-induced NLRP3 activation, as demonstrated by decreased expressions of NLRP3 and matured caspase-1 and IL-1β, and also alleviated glial proliferation and dopaminergic neuronal degeneration. Notably, TBA recovered acetylation levels of Prx2 and reduced oxidative stress. Conclusion Our findings indicate that pharmacological inhibition of HDAC6 with TBA attenuates NLRP3 inflammation and protects dopaminergic neurons, probably through Prx2 acetylation. This study suggests that the deacetylase catalytic domain of HDAC6 is a potential target for PD treatment.